The dependence of sustainable economic growth on the complex of factors in hydrocarbons-exporting countries. (December 2020) - Filimonova, I.V.; Cherepanova, D.M.; Provornaya, I.V.; Kozhevin, V.D.; Nemov, V.Y.
Abstract: The analysis of factors affecting economic growth in different countries is fundamental for forecasting and strategic development of the economy. The increasing dependence of the world economy on the volatile conjuncture of world energy markets exacerbates the discussion about the role of resource dependence in economic development. At the same time, sustainable development is one of the priority goals in development models of many countries. Therefore, the purpose is to assess the influence of resource dependence factors and factors of sustainable growth on the economic growth of the net oil and gas exporting countries. To achieve the purpose of the study a panel data analysis method was used. The sample consists of 41 countries, which are the net exporters of hydrocarbons, for the period 1990–2018. Countries are classified by macro-regions. The authors confirmed that the influence of resource dependence factors is not significant for some hydrocarbons exporting countries. However, the growth of the economy of most countries is significantly dependent on factors of sustainable growth. Resource-dependent countries need diversification of their economies and government revenues. Given the trends of low-carbon development and improvement of climate policies, the accelerated dynamics of the development of "green" energy is essential.